Do Preoperative Nasal Antiseptic Swabs Reduce the Rate of Surgical Site Infections After Adult Thoracolumbar Spine Surgery?. (September 2021) - Buyuk, Abdul Fettah; Tam, Harrison K.; Dawson, John M.; Mehbod, Amir A.; Transfeldt, Ensor E.; Alcala, Christopher
Abstract : Introduction: Surgical site infection (SSI) remains a major complication after adult spinal surgery. We investigated whether adding preoperative nasal decontamination by antiseptic swab (skin and nasal antiseptic povidone-iodine, SNA-PI) to our antimicrobial protocol reduces the SSI rate among our patients undergoing thoracolumbar spinal surgery. Methods: We retrospectively reviewed all adult thoracolumbar spinal surgeries performed between June 2015 and May 2017 at a single hospital. Patients were divided into those who received nasal decontamination (SNA-PI+) and those who did not (SNA-PI−). SSI rates and responsible pathogens were compared between the cohorts. Results: A total of 1, 555 surgeries with nasal decontamination (SNA-PI+) and 1, 423 surgeries without (SNA-PI−) were included. The SSI rate in the SNA-PI+ group was 13 of 1, 555 (0.8%) versus 10 of 1, 423 (0.7%) for SNA-PI− group ( P = 0.68). The infection rate was the highest among posterior instrumented fusions in the SNA-PI+ group (1.4%). Methicillin-sensitive Staphylococcus aureus was responsible for 70% of infections in the SNA-PI− group and 38% in the SNA-PI+ group ( P = 0.13). Conclusions: Routine nasal antiseptic swab before spine surgery did not affect the overall rate of SSI in thoracolumbar spinal surgeries. The incidence of methicillin-sensitive S aureus was lower in patients who received nasal decontamination (5/1, 555, 0.3%) compared with those who did not (7/1, 423, 0.5%); however, this result was not statistically significant ( P = 0.57).